App-based support for breast cancer patients to reduce psychological distress during therapy and survivorship – a multicentric randomized controlled trial - Wolff, Josefine; Seidel, Svenja; Wuelfing, Pia; Lux, Michael Patrick; Eulenburg, Christine zu; Smollich, Martin; Baumann, Freerk; Seitz, Stephan; Kuemmel, Sherko; Thill, Marc; Tio, Joke; Braun, Michael; et al. (Frontiers in Oncology, 2024)
The negative impact of unmanaged psychological distress on quality of life and outcome in breast cancer survivors has been demonstrated. Fortunately, studies indicate that distress can effectively be addressed and even prevented using evidence-based interventions. In Germany prescription-based mobile health apps, known as DiGAs (digital health applications), that are fully reimbursed by health insurances, were introduced in 2020. In this study, the effectiveness of an approved breast cancer DiGA was investigated: The personalized coaching app PINK! Coach supports and accompanies breast cancer patients during therapy and follow-up. Methods PINK! Coach was specifically designed for breast cancer (BC) patients from the day of diagnosis to the time of Follow-up (aftercare). The app offers individualized, evidence-based therapy and sideeffect management, mindfulness-based stress reduction, nutritional and psychological education, physical activity tracking, and motivational exercises to implement lifestyle changes sustainably in daily routine. A prospective RCT was performed with n = 434 patients recruited in 7 German breast cancer centers. Patients with BC were included independent of their stage of diseases, type of therapy and molecular characteristics of the tumor. Patients were randomized into one of two groups: The intervention group got access to PINK! over 12 weeks; the control group served as a waiting-list comparison to "standard of care." The primary endpoint was psychological distress objectified by means of Patient Health Questionnaire-9 (PHQ-9). Subgroups were defined to investigate the app's effect on several patient groups. Efficacy analysis of the primary endpoint revealed a significant reduction in psychological distress (least squares estimate -1.62, 95% confidence interval [1.03; 2.21]; p<0.001) among intervention group patients from baseline to T3 vs, control group. Subgroup analysis also suggested improvements across all clinical situations.Patients with breast cancer suffer from psychological problems including anxiety and depression during and after therapy. Personalized, supportive care with the app PINK! Coach turned out as a promising opportunity to significantly improve psychological distress in a convenient, accessible, and low-threshold manner for breast cancer patients independent of their stage of disease (EBC/MBC), therapy phase (aftercare or therapy) or therapy itself (chemotherapy/other therapy options). The app is routinely available in Germany as a DiGA.